Islamic transformation centre for enhancing the Qur’anic and entrepreneurship knowledge and skills among youth: a conceptual solution - Mazlan, Mahfizah; Mohd Zarani, Nurul Aqilah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2016)
The purpose of this project is to enhance the Quranic and entrepreneurship knowledge and skills of Muslim youth via an Islamic Transformation Center (ITC) by leveraging the Quadruple Helix Model (QHM)collaboration approach where the actors are the government, university, industry and citizen; and with the use of Information and Communication Technology (ICT). This paper intends to propose a conceptual ITC as a platform in developing holistic potential of individuals who are intellectually, spiritually, emotionally and physically balanced, based on firm belief and devotion to God. This paper is based on literature reviews, adopting the Business Model Canvas (BMC) framework in building a conceptual solution for Quranic and entrepreneurship knowledge and skills for youth development. This conceptual paper seeks to put forth a collaboration approach, namely the combined deployment of the Quadruple Helix Model (QHM) mooted by Agency Inovasi Malaysia, the concept of Whole-of-Government (WoG) implementation across the Malaysian Government Agency, also supported by the Network of Mosque (NoM) and the use of ICT. In order to introduce Quranic and entrepreneurship knowledge and skills to the youths effectively, the integration of governments, professionals, academia, industry and citizen supported by the use of ICT are required in order to leverage Quranic and entrepreneurship knowledge and skills. Youths are expected to play an important role for the advancement of Islam as well as the enhancement of societal wellbeing.